PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI LUAR PENGADILAN - Salmudin (Legalita, 2019)
Sustainable development always causes changes to the environment, which causes damage. In order to resolve problems with those who have polluted the environment, it is done through the courts (Litigation) and through out of court (Non Litigation), while the settlement through the courts, can be done through the means of criminal law, civil law and administrative law . The problem in this article itself is First, how is the settlement of environmental disputes outside the court in civil law matters? Second, what are the obstacles in resolving environmental disputes outside the court? This article uses a normative approach to further analyze data qualitatively. Out-of-Court Dispute Settlement is actually held to reach agreement on the form and the amount of compensation, and / or certain actions, to ensure there is no occurrence or recurrence of negative impacts on the environment. The obstacles that are often faced by the settlement of environmental disputes outside the court are mainly related to the nominal and the form of compensation due to differences in views between pollutants and prosecutors. Another obstacle is the difficulty of administrative law enforcement in the context of environmental management, when faced with administrative decisions in the form of revocation of business licenses that will have a sociological economic impact causing pressure from the community / Non-Governmental Organizations (NGOs) to submit cases of pollution and damage to court hearings.